Highly Efficient Regeneration of Bombax ceiba via De Novo Organogenesis from Hypocotyl and Bud Explants - Yamei Li; Qionghai Jiang; Lisha Cha; Fei Lin; Fenling Tang; Yong Kang; Guangsui Yang; Surong Huang; Yuhua Guo; Junmei Yin (Plants)
Bombax ceiba is an important medicinal and ornamental tree widely distributed in tropical and subtropical areas. However, its seeds lose viability rapidly after harvest, which has created hurdles in large-scale propagation. Here, we describe the development of a rapid and efficient de novo organogenesis system for Bombax ceiba, incorporating both indirect and direct regeneration pathways. The optimal basal medium used throughout the protocol was ½ MS supplemented with 30 g/L glucose, with all cultures maintained at 26–28 °C. For the indirect pathway, callus was induced from both ends of each hypocotyl on basal medium supplemented with 0.2 mg·L−1 2,4-dichlorophenoxyacetic acid (2,4-D) and 0.5 mg·L−1 6-Benzylaminopurine (6-BA) under dark conditions. The induced calluses were subsequently differentiated into adventitious shoots on basal media containing 0.5 mg·L−1 Indole-3-butyric acid (IBA), 0.15 mg·L−1 Kinetin (KIN), and 1 mg·L−1 6-BA under a 16 h photoperiod, resulting in a callus induction rate of 140% and a differentiation rate of 51%. For the direct regeneration pathway, shoot buds cultured on medium with 0.5 mg·L−1 IBA and 1 mg·L−1 6-BA achieved a 100% sprouting rate with a regeneration coefficient of approximately 3.2. The regenerated adventitious shoots rooted successfully on medium supplemented with 0.5 mg·L−1 Naphthylacetic acid (NAA) and were acclimatized under greenhouse conditions to produce viable plantlets. This regeneration system efficiently utilizes sterile seedling explants, is not limited by seasonal or environmental factors, and significantly improves the propagation efficiency of Bombax ceiba. These optimized micropropagation methods also provide a robust platform for future genetic transformation studies using hypocotyls and shoot buds as explants.